2020
DOI: 10.3389/fnut.2020.571455
|View full text |Cite
|
Sign up to set email alerts
|

Do Olive and Fish Oils of the Mediterranean Diet Have a Role in Triple Negative Breast Cancer Prevention and Therapy? An Exploration of Evidence in Cells and Animal Models

Abstract: Breast cancer is the most common malignancy and cause of cancer-related mortality among women worldwide. Triple negative breast cancers (TNBC) are the most aggressive and lethal of the breast cancer molecular subtypes, due in part to a poor understanding of TNBC etiology and lack of targeted therapeutics. Despite advances in the clinical management of TNBC, optimal treatment regimens remain elusive. Thus, identifying interventional approaches that suppress the initiation and progression of TNBC, while minimizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 139 publications
(254 reference statements)
0
18
0
4
Order By: Relevance
“…There is a large body of evidence suggesting the chemo-preventive effect of ω-3 FA against BCa and other cancer development [see recent reviews and meta-analysis ( Mokbel and Mokbel, 2019 ; Nindrea et al, 2019a , b ; Donovan et al, 2020 ; Yurko-Mauro et al, 2020 )]. Hardman’s group earlier reported that maternal diet supplemented with canola oil (ω-3 FA-rich) reduced tumor incidence and growth in C3(1)-TAg mice offspring ( Ion et al, 2010 ), suggesting the involvement of possible transgenerational epigenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of evidence suggesting the chemo-preventive effect of ω-3 FA against BCa and other cancer development [see recent reviews and meta-analysis ( Mokbel and Mokbel, 2019 ; Nindrea et al, 2019a , b ; Donovan et al, 2020 ; Yurko-Mauro et al, 2020 )]. Hardman’s group earlier reported that maternal diet supplemented with canola oil (ω-3 FA-rich) reduced tumor incidence and growth in C3(1)-TAg mice offspring ( Ion et al, 2010 ), suggesting the involvement of possible transgenerational epigenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The MeD originated in Italy and Greece in the 1960s [7] and describes the dietary patterns of countries and 1 2, 3 4 5 6 7 8, 9 10 11, 12, 5, 13 14 15 cultures bordering the Mediterranean Sea. The diet is abundant in plant-based foods rich in complex carbohydrates, such as whole grains, legumes, nuts, beans, vegetables, fruits, herbs, and spices; emphasizes fish, poultry, and lean sources of protein over red and processed meat; uses healthy fat (olive oil) as the principal source of fat; and includes a moderate intake of low-fat dairy and alcohol (mostly red wine) with meals [8].…”
Section: Review Mediterranean Diet In Breast Cancer Preventionmentioning
confidence: 99%
“…The risk reduction of BC was found to be 68% (87-21%) for the MeD with extra virgin olive oil (EVOO) group compared to the control diet group rich in low-fat foods [10]. Several other studies, including clinical trials and observational studies, have also demonstrated an inverse association between the MeD and BC [8,[11][12][13][14].…”
Section: Review Mediterranean Diet In Breast Cancer Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish oil is rich in omega-3 (α-Linolenic acid), wheat germ oil is rich in omega-6 (Linoleic acid), and omega-9 (Oleic acid) is mainly present in olive oil (Balić et al, 2020;Donovan et al, 2020). Some kinds of dietary patterns result in elevated consumption of omega-6 fatty acid than omega 3 fatty acid resulting in obesity and high risk of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%